Consistency of Renal Stone Volume Measurements Across CT Scanner Model and Reconstruction Algorithm Configurations - Huang, Alice E; Montoya, Juan C; Shiung, Maria; Leng, Shuai; McCollough, Cynthia H (American journal of roentgenology (1976), 2017)
The objective of this prospective study is to evaluate the consistency of renal stone volume estimation using dual-energy CT across scanner model and reconstruction algorithm configurations. Patients underwent scanning with routine kidney stone composition protocols on both second- and third-generation dual-source CT scanners. Images were reconstructed using filtered back projection and iterative reconstruction (IR). In addition, a modified IR kernel on the third-generation CT scanner was evaluated. Individual kidney stone volumes were determined and compared. No significant difference was noted in measured volumes between filtered back-projection data, IR data from the second-generation scanner, and the modified IR kernel data (p > 0.05). The third-generation commercially available IR kernel yielded lower volumes than did the other configurations (p < 0.0001). With the use of a modified kernel for the third-generation scanner, patients being monitored for changes in kidney stone volume can undergo scanning performed with second- or third-generation dual-energy CT scanners, and the images obtained can be reconstructed with either filtered back projection or IR without the introduction of bias into kidney stone volume measurements.